Detector station and registering system of the NEVOD-EAS array cluster. Issue 3 (January 2016) - Shulzhenko, I A; Ampilogov, N V; Astapov, I I; Chiavassa, A; Khokhlov, S S; Kompaniets, K G; Kutovoy, V Yu; Likiy, O I; Yashin, I I
Abstract: The design features of the detector stations of the cluster type shower array NEVOD-EAS which is now under construction on the basis of the Unique Scientific Facility 'Experimental complex NEVOD', as well as the operation principle of the cluster registering system are discussed.